Spatio-Temporal Variability of Peat CH4 and N2O Fluxes and Their Contribution to Peat GHG Budgets in Indonesian Forests and Oil Palm Plantations - Swails, Erin; Hergoualc’h, Kristell; Verchot, Louis; Novita, Nisa; Lawrence, Deborah (Frontiers in Environmental Science, 2021)
Land-use change in tropical peatlands substantially impacts peat emissions of methane (CH4) and nitrous oxide (N2O) in addition to emissions of carbon dioxide (CO2). However, assessments of full peat greenhouse gas (GHG) budgets are scarce and CH4 and N2O contributions remain highly uncertain. The objective of our research was to assess changes in peat GHG flux and budget associated with peat swamp forest disturbance and conversion to oil palm plantation and to evaluate drivers of variation in trace gas fluxes. Over a period of one and a half year, we monitored monthly CH4 and N2O fluxes together with environmental variables in three undrained peat swamp forests and three oil palm plantations on peat in Central Kalimantan. The forests included two primary forests and one 30-year-old secondary forest. We calculated the peat GHG budget in both ecosystems using soil respiration and litterfall rates measured concurrently with CH4 and N2O fluxes, site-specific soil respiration partitioning ratios, and literature-based values of root inputs and dissolved organic carbon export. Peat CH4 fluxes (kg CH4 ha−1 year−1) were insignificant in oil palm (0.3 ± 0.4) while emissions in forest were high (14.0 ± 2.8), and larger in wet than in dry months. N2O emissions (kg N2O ha−1 year−1) were highly variable spatially and temporally and similar across land-uses (5.0 ± 3.9 and 5.2 ± 3.7 in oil palm and forest). Temporal variation of CH4 was controlled by water table level and soil water-filled pore space in forest and oil palm, respectively. Monthly fluctuations of N2O were linked to water table level in forest. The peat GHG budget (Mg CO2 equivalent ha−1 year−1) in oil palm (31.7 ± 8.6) was nearly eight times the budget in forest (4.0 ± 4.8) owing mainly to decreased peat C inputs and increased peat C outputs. The GHG budget was also ten times higher in the secondary forest (10.2 ± 4.5) than in the primary forests (0.9 ± 3.9) on the account of a larger peat C budget and N2O emission rate. In oil palm 96% of emissions were released as CO2 whereas in forest CH4 and N2O together contributed 65% to the budget. Our study highlights the disastrous atmospheric impact associated with forest degradation and conversion to oil palm in tropical peatlands and stresses the need to investigate GHG fluxes in disturbed undrained lands.